Deposition and patterning of gold nanostructures on various wettable and nonwettable patterned surfaces. (21st November 2019) - Ahmad, Imtiaz; Jan, Rahim; Khan, Hidayat Ullah; Khan, Sajjad Ahmad; Hussain, Akhlaq
Abstract: Suspensions comprises of gold nanostructures deposited on a number of alternating wettable silicon dioxide (SiO2 ) and nonwettable perfluorodecyltrichlorosilane (PFDTS) patterned surfaces via droplet evaporation technique. On such surfaces during evaporation of aqueous phase, three-phased contact line of a droplet deposit nanoparticles preferentially on the wettable set of stripes and consequently leads to nanoparticles patterning over the substrate. The presence of the nonwettable stripes on both sides of the wettable stripe on such patterned substrates will push the liquid towards the wettable stripe. Such liquid drive will induce hydrodynamic confinement effect. This hydrodynamic confinement will produce nanoparticle patterns that will merely decorate wettable stripes with gold nanorod deposits. Aligned arrays of gold nanorods are observed near the interfacial boundaries. Ribbon-like arrays of face-to-face aligned nanorods are observed in some locations within the deposits. In case of citrate-stabilized gold nanospheres (diameter∼10 nm), bonding sites for nanospheres on the wettable stripes are provided by the self-assembled monolayers of 3-triethoxysilylpropylamine (APTES). The presence of APTES will facilitate gold nanoparticles deposition (monolayer) on the wettable stripes whereas nonwettable stripes demonstrated agglomerated and mobilized bunches of nanoparticles. As such nanoparticle clusters are unstable on the PFDTS surface, hence can be removed by air blowing mechanism. The air rushing across the substrate removes nearly all nanoparticles settled over the nonwettable stripes whereas nanoparticle arrangement on the wettable region remains unaltered.